A Modified Binary Firefly Algorithm to Solve Hardware/Software Partitioning Problem (Informatica, 2021)
Hardware/Software (Hw/Sw) partitioning is a crucial step in Hw/Sw co-design that determines which components of the embedded system could be implemented on hardware and which ones on software. It aims to find a design implementation that fulfils all the specification requirements (functionality, goals and constraints) with a low cost. Most formulations of Hw/Sw partitioning dilemma have proven to NP-hard optimization problem. The firefly algorithm (FA) emerges as a significant tool of Swarm Intelligence that has been applied in many areas of optimization. The main purpose of this paper is to present a modified binary firefly algorithm to solve Hw/Sw partitioning problems. Results are compared with other well-known metaheuristic algorithms: Binary Differential Evolution (BDE) , Discrete Differential Evolution(DDE), Self-adaptive differential evolution algorithm (saBDE), New Modified Binary Differential Evolution (NMBDE), New Binary Differential Evolution(NBDE) , Particle Swarm Optimization Algorithm (PSO), and Genetic Algorithm (GA). The computational results show that it produced better results than the all used algorithms.